Underuse of recommended treatments among people living with treatment-resistant psychosis - Lappin, Julia M.; Davies, Kimberley; O'Donnell, Maryanne; Walpola, Ishan C. (Frontiers in Psychiatry, 2022)
Background: International guidelines recommend that individuals with treatment-resistant psychosis be treated with clozapine. ECT has also been reported to improve symptom profile. Identification of clozapine and/or ECT use in real-world practice enables understanding of the extent to which this evidence-base is implemented. Setting: Statewide public health tertiary referral service, the Tertiary Referral Service for Psychosis (TRSP), NSW, Australia. Objectives: To i) describe clinical characteristics of individuals with treatment-resistant psychosis and to detail the proportion who had received a trial of clozapine or ECT at any point during their illness course; ii) describe the characteristics of the treatment trials in both those currently on clozapine and those previously on clozapine; iii) document reasons in relevant individuals why clozapine had never been used. Methods: All TRSP clients who met criteria for treatment-resistance (TR) were included. A detailed casenote review was conducted to examine whether clozapine and/or ECT had ever been prescribed. Characteristics of clozapine and ECT trials were documented. Tertiary service psychopharmacological recommendations are described. Findings: 36 of 48 individuals had TR, with marked clinical and functional impairment. A minority were receiving clozapine (n=14/36). Most had received a clozapine trial at some point (n=32/36). Most experienced persistent clinical symptoms while on clozapine (n= 29/32). Clozapine plasma levels were very rarely reported (4/32). Augmentation and antipsychotic polypharmacy were common among those currently on clozapine. Median clozapine trial duration was 4.0 (IQR: 3.0-20.3) months in individuals previously prescribed clozapine. Reasons for clozapine discontinuation included intolerable side effects (n=10/18) and poor adherence (n=7/18). One-quarter of TR-individuals had trialed ECT (n=9/36). Tertiary service recommendations included routine plasma monitoring to optimize dose among people currently on clozapine; clozapine retrial in those previously treated; and clozapine initiation for those who had never received clozapine. ECT was recommended to augment clozapine and as an alternative where clozapine trial/retrial was not feasible. Conclusions: Among people with TR referred to a tertiary service, clozapine and ECT were underutilized. Clozapine trials typically terminated without an adequate trial. Strategies to optimize use of clozapine therapy and ECT in clinical settings are needed to increase therapeutic effectiveness of evidence-based therapies for treatment resistant psychosis.